Identification, analysis and prediction of valid and false information related to vaccines from Romanian tweets - Valeanu, Andrei; Mihai, Dragos Paul; Andrei, Corina; Puscasu, Ciprian; Ionica, Alexandra Mihaela; Hinoveanu, Miruna Ioana; Predoi, Valentina Patricia; Bulancea, Ema; Chirita, Cornel; Negres, Simona; Marineci, Cristian Daniel (Frontiers in Public Health, 2024)
Introduction The online misinformation might undermine the vaccination efforts. Therefore, given the fact that no study specifically analyzed online vaccine related content written in Romanian, the main objective of the study was to detect and evaluate tweets related to vaccines and written in Romanian language. Methods 1,400 Romanian vaccine related tweets were manually classified in true, neutral and fake information and analyzed based on wordcloud representations, a correlation analysis between the three classes and specific tweet characteristics and the validation of several predictive machine learning algorithms. Results and discussion The tweets annotated as misinformation showed specific word patterns and were liked and reshared more often as compared to the true and neutral ones. The validation of the machine learning algorithms yielded enhanced results in terms of Area Under the Receiver Operating Characteristic Curve Score (0.744–0.843) when evaluating the Support Vector Classifier. The predictive model estimates in a well calibrated manner the probability that a specific Twitter post is true, neutral or fake. The current study offers important insights regarding vaccine related online content written in an Eastern European language. Future studies must aim at building an online platform for rapid identification of vaccine misinformation and raising awareness for the general population.